Achieving Consensus in the South China Sea: Explaining Bilateralism's Bane and Multilateralism's Boon - Maulaya, Mahbi (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2020)
A prolonged debate arises whether bilateralism or multilateralism is the most effective path to achieve mutual consensus among parties in the South China Sea dispute. This study identifies bilateral approach negativity to settle such a complex and overlapping dispute existed in that area grounded by two considerations. First, bilateralism is a non-transparent scheme of bargaining process. Due to bilateral implementation only conducted by two states, the more powerful actor will escape from the scrutiny of others, thus making it possesses the opportunity to put forward discriminatory bid and robust sphere to suppress other party’s stance. The bilateral approach would result in a non-consensus agreement for less powerful parties. Second, the conflictual area draws the involvement of more than three sovereign parties with overlapping claims. Multilateralism, negotiation framework for multi-parties, is the most, perhaps the only, promising path to ease the existing tension numerous parties into the stage of consensus. Moreover, multilateralism may present positive norms – transparency and non-unilateralism – that could guide the involving parties to create consensus. The analysis of this paper obtained from utilization of qualitative data, library research methods, and by the comprehension of three conceptual frameworks, bilateralism, multilateralism, and consensus.